KONTRIBUSI MA’HAD ALY TERHADAP PEMAHAMAN KEISLAMAN MELALUI PENDIDIKAN AGAMA ISLAM DI INDONESIA - Yusmei, Nining; Iswantir, Iswantir (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
Writing this article aims to examine the contribution of Ma'had Aly through the education system such as curriculum, educational methods, the basis for implementing Islamic religious education in ma'had aly and variations in the development of Islamic boarding schools' academic traditions in ma'had aly. This study utilizes a qualitative descriptive method. Therefore, the analysis used in reading and interpreting qualitative data. Sources of data were collected from journal materials, articles and websites that are relevant to this study. so that it can be concluded that Ma'had Aly is part of the pesantren function to awaken the community to have idealism, intellectual ability, and noble behavior (al-Akhlâq al-Karîmah) ​​in order to organize and build a complete national character. If seen from the mapping of education, ma'had aly includes formal diniyah education, in which case the government has issued several policies related to Islamic religious education in Ma'had Aly and in the ma'had aly style education system this is a form of effort to creating scholars who will be able to provide a correct understanding of Islam in accordance with Islamic teachings.